4.(i)  Factorise :

  (i)    12x^2 - 7x + 1

Answers (1)
G Gautam harsolia

Given polynomial is   12x^2 - 7x + 1

We need to factorise the middle term into two terms such that their product is equal to 12 \times 1 = 12 and their sum is equal to -7

We can solve it as 

\Rightarrow 12x^2 - 7x + 1

\Rightarrow 12x^2-3x-4x+1                                                       (\because -3 \times -4 = 12 \ \ and \ \ -3+(-4) = -7)

\Rightarrow 3x(4x-1)-1(4x-1)

\Rightarrow (3x-1)(4x-1)                             

Exams
Articles
Questions